Pendampingan Pembuatan Soal dengan Teknologi Artificial Intelligence - Hosniyeh, Hosniyeh; Mahfudloh, Qoriatul (Lembaga Penerbitan dan Publikasi Ilmiah, 2025)
This community service activity aims to improve teachers' understanding and skills in utilizing artificial intelligence (AI)-based learning technology to support the effectiveness of the learning process. Held at MA Raudlatul Ulum 2 Putukrejo, this activity was motivated by low digital literacy and limited use of AI technology among teachers. The implementation method included a pre-test, material delivery, a practical workshop on using AI applications such as MagicformApp, Quizgecko, Kahoot, Quizizz, and Readworks, a presentation of the practical results, a post-test, and an activity evaluation. The results showed an increase in participants' knowledge of various AI platforms that can be used to automatically generate questions. In addition to providing new experiences, this training also encouraged teachers' independence in creating learning evaluation materials. The main obstacles faced included limited technological infrastructure and a ban on students using digital devices in the Islamic boarding school environment. Nevertheless, this training made a significant contribution in broadening teachers' horizons about the application of AI in learning. It is recommended that this activity be held on an ongoing basis with the support of facilities and further training.